2014
DOI: 10.1371/journal.pone.0101441
|View full text |Cite
|
Sign up to set email alerts
|

CD127 Expression, Exhaustion Status and Antigen Specific Proliferation Predict Sustained Virologic Response to IFN in HCV/HIV Co-Infected Individuals

Abstract: Hepatitis C virus (HCV) infection is a major cause of morbidity and mortality in the HIV co-infected population. Interferon-alpha (IFN-α) remains a major component of anti-HCV therapy despite its deleterious effects on the immune system. Furthermore, IFN-α was recently shown to diminish the size of the latent HIV reservoir. The objectives of this study were to monitor the impact of IFN-α on T cell phenotype and proliferation of HIV and HCV-specific T cells during IFN therapy, and to identify immune markers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…In contrast, interferon-a does not seem to affect the proportion of T cells expressing IL-7Ra. Thus, we found no effect of PEG/ R AE 1.PI treatment on the proportion of IL-7Ra+ T cells and a decrease in the proportion of IL-7Ra+ T cells post SVR which is in agreement with previous studies (23,25). Furthermore, the reduced proportion of IL-7Ra+ T cells post SVR is consistent with our previous study demonstrating higher proportions of IL-7Ra+ CD4+ T cells in chronic HCV patients with fibrosis compared to healthy controls (16).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, interferon-a does not seem to affect the proportion of T cells expressing IL-7Ra. Thus, we found no effect of PEG/ R AE 1.PI treatment on the proportion of IL-7Ra+ T cells and a decrease in the proportion of IL-7Ra+ T cells post SVR which is in agreement with previous studies (23,25). Furthermore, the reduced proportion of IL-7Ra+ T cells post SVR is consistent with our previous study demonstrating higher proportions of IL-7Ra+ CD4+ T cells in chronic HCV patients with fibrosis compared to healthy controls (16).…”
Section: Discussionsupporting
confidence: 93%
“…Stimulation of IL-7R causes elevated levels of Bcl-2 that decreases the susceptibility of cell apoptosis which is illustrated in the present data with the decreased proportion of IL-7Ra+ T cells and higher proportion of apoptotic T cells after SVR. These changes may also be affected by an alteration in immune activation (25,26). However, we investigated LPS in plasma as a measurement of microbial translocation and the expression of CD38 on CD8+ T cells as a measurement of chronic immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + T cells elicited in response to coinfections exhibit a more exhausted phenotype compared to cells from monoinfections ( 104 , 105 ). A study by Vali et al compared PD-1 and TIM-3 coexpression on HCV-specific CD8 + T cells during HIV/HCV coinfection ( 106 ).…”
Section: Chronic Infections and Coinhibitory Receptor Expressionmentioning
confidence: 99%
“…[23][24][25] We previously reported that in HCV-infected LT recipients undergoing protocolized T cell proliferative responses. [28][29][30] What was unexpected in our study was the finding that HCV infection had a stronger impact on antidonor CD8 + T cell responses than on those directed against Although the prevalence of clinically apparent immune-mediated events was low, it should be taken into account that many clinicians routinely increase the doses of immunosuppressive drugs in patients receiving anti-HCV medications. Furthermore, in the absence of protocolized liver biopsies it is not possible to exclude the development of subclinical rejection-type liver allograft damage, which is much more frequent than originally thought.…”
Section: Discussionmentioning
confidence: 64%